(untitled) (Journal of Partial Differential Equations, 2003)
" American options give holder a right to exercise it at any time at will, the holder should to make the exercise policy in such a way that the expected payoff from the option will be maximized. In this note we prove that it is equivalent to a fact which makes the option value and option delta continuous."